Nacjonalizm polski w optyce niemieckiej lat trzydziestych XX w. - Stachowiak, Paweł (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2016)
German interest in Polish nationalism was negligible in the nineteen thirties. Only the magazines and publications dealing with Eastern European issues devoted more time and space to Polish nationalism. They practically ignored the NSDAP sources. The issue of relations between Polish nationalism on the one hand and fascism and national socialism on the other has become the topic of academic research. So far, Germany at that time has never been analyzed in this context. A question worth considering is whether German journalism and academic publications were interested in the development of Polish nationalism. How did the proponents of the Nazi movement perceive their Polish ideological counterparts? What was the attitude of non-Nazi journalists and scholars? The aim of this paper is to try to complement the studies in the history of mutual relations of Polish and German nationalism.

Niemieckie zainteresowanie polskim nacjonalizmem było w latach trzydziestych niewielkie. Więcej miejsca i uwagi poświęcały mu jedynie czasopisma i wydawnictwa zajmujące się szczególnie problematyką wschodnioeuropejską. Niemal całkowicie pomijały oficjalne źródła NSDAP.Problem relacji między polskim nacjonalizmem a faszyzmem i narodowym socjalizmem stał się przedmiotem refleksji naukowej. Niestety jak dotąd nie dokonano podobnej analizy biorąc jako punkt wyjścia Niemcy ówczesnej epoki. Warto zadać pytanie, czy również tam, w publicystyce, w publikacjach naukowych, rozwój polskiego nacjonalizmu wzbudzał zainteresowanie? Jak postrzegali swych polskich ideowych pobratymców zwolennicy ruchu nazistowskiego, jak odnosili się do nich publicyści i naukowcy proweniencji nienazistowskiej? Zadaniem niniejszego tekstu jest próba takiego uzupełnienia stanu badań nad dziejami wzajemnych odniesień nacjonalizmów w Polsce i Niemczech.
Polish nationalism in the German eyes of the thirties
Keywords: polski nacjonalizm; III Rzesza; nazizm; narodowy socjalizm; Polish nationalism; Third Reich; Nazism; National Socialism